Antenatal diagnosis of omphalocele and spinal dysraphism: a possible OEIS complex - Khanna, Dolly; Bhatti, Karandeep S. (International Journal of Research in Medical Sciences, 2020)
OEIS complex, which comprises of omphalocele, exstrophy bladder, imperforate anus and spinal dysraphism, is a rare disorder. The prognosis depends upon the severity of the structural defects. Survival depends on the extension of the cloacal exstrophy and the neural tube defect. The antenatal diagnosis in early pregnancy is very tough, and a high level of suspicion should be kept for the possibility of its existence, even only if omphalocele and spinal dysraphism are seen on a prenatal sonography. Authors present the case of a 33-year-old, G1P0 female, who on her prenatal routine sonography scan, was found to have a fetus with omphalocele and spinal dysraphism. Despite the repeated attempts to follow her up, she refused and hence the possibility of the presence of other associated malformations could not be ascertained. Considering the difficulty of antenatal diagnosis of OEIS complex and its associated mortality, the objective of this case report is to discuss the vital sonographic findings of OEIS, along with its etiology and prognosis, which can aid in its early detection and subsequently help parents to make a decision regarding the continuation of pregnancy.